YATROGENES IN NEONATOLOGY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
The problem of iatrogenesis has become relevant not only in adult practice, where self-treatment takes place, but also in neonatology and pediatrics. Children developed diseases and pathological conditions due to unjustified prescription of pharmaceutical drugs. They are the result of side effects of medications, their components, impurities, and undesirable combinations of medications. In the absolute majority of cases, they require additional medication correction, and in a number of cases, can lead to serious health disorders and a decrease in the quality of life. Providing medical assistance is a complex form of professional activity. It requires deep special knowledge, practical skills, and high spiritual qualities. However, a medical worker may be mistaken because they are dealing with the most complex object of nature - the human body, especially the child's body.